Muniz Freire e o desenvolvimento geográfico desigual no Espírito Santo : a construção de uma herança político-ideológica no território capixaba - Marchese, Vinicius Francisco (2017)
This dissertation will deal with the Geo-History of Espírito Santo and the influence that José de Melo Carvalho Muniz Freire, President of the State for two mandates (1892-1896 and 1900- 1904), had in the insertion of this territory in a logic of Uneven Geographical Development. In view of the prerogatives still observable today of a noticeable political-economic imbalance between the capital and the rest of Espírito Santo, The research proposed here, will seek to identify the point of inflection in this territorial organization, in which the political capital, Vitória, also acquires cultural and economic character, centralizing all the powers in this city and relegating the other areas to barely auxiliaries: territories integrated and subservient to the "Crib City". For that, concepts and theories of geographers such as David Harvey, Neil Smith and Milton Santos, will be used to justify the hypotheses proposals, as well as academic works (dissertations and theses) and classic and recent works of the capixaba historiography, serving as the basis for the reports that will be settled down. Thus, in order to construct such reports and later analyze them, a resumption of local history, a kind of attempt to register part of the an inheritance to which the first governors of this new period in Espírito Santo would have access. When the beginning of state republicanism is reached, the context here will be observed, such as its economy, productive structure, social aspects, among other topics considered key to an understanding of what the state was like at the turn of the nineteenth to the twentieth centuries. Thereafter in will be observed the two mandates of Muniz Freire in front of the territory and his main achievements, notably the confection of the Novo Arrabalde Project and the structuring of a new logic of traffic and transportation based on the railway sector and the reform, expansion and equipment of the Port of Vitória. Thus, it is believed that, from the analysis of the role that this Govern had for the State, being considered by many a of the main capixaba political figures, as well as from the analysis of his positivist ideal embodied in discourses of a modernizing nature and very pretentious works for the time, it will be possible to observe with clarity the changes in the capixaba Territorial Division of Labor, before ruled by the territory, Cachoeiro de Itapemirim to the south and São Mateus to the north, to the capital, adding to the close bond created between this city and the neighboring State to the west, Minas Gerais. In short, what we intend to demonstrate in this work is the journey of local history and its change of route based on political-economic aspects of a character that epitomized the ideals of the time and the yearnings of the local elite, even if, for this, he has immersed the Espírito Santo in a structure based on the Uneven Geographical Development.